(3QSGdI aj GdMSGH GdghGfis - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf,J (B675 (3g` s
(3ChdgG (B:s
(3gPg QSGdI ai GdMSGH GdghGFi MQQgG edc GdMceGA fLe GdOjf GdcGJHi QMeI Gddg Ydjg HGdfGS HYV GcGHQ GdReGf s
(3BNQgG (B:s
(3GdaUd GdKGdK YTQ ai GNQGL VdY GdedYH CNPfG VdYgG HGdWQjb GdPi eQ ai GdGYOGO aeG NQL agh GdObGFb hgPG BNQ eG GQOfG PcQg ai gPg GdQSGdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B159s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(3/7189) s
Keywords: (3GdQjGVjGJs